Perancangan Model Bisnis Kaki Bukit Coffee Menggunakan Metode Business Model Canvas - Achmad, Fadhil; Aryani, Sinta; Sulistyo, Budi (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Kaki Bukit Coffee is a coffee shop located in West Bandung Regency, precisely on Jl. Maribaya No.16, Kayuambon, Lembang District, which was founded on December 16 2018. This coffee shop offers various types of drinks, both hot and cold, such as Basic Coffee, Flavored Coffee, Freshener, and Tea. However, Kaki Bukit Coffee faces several challenges, including not achieving its revenue target. This challenge is caused by several factors such as lack of employee capability, limited space capacity, lack of product innovation, many competitors, the influence of rainy weather, less than optimal promotional strategies, and limited use of promotional media only via Instagram. This research aims to identify and overcome the problems faced by Kaki Bukit Coffee through evaluating and designing a new business model using the Business Model Canvas (BMC) method. The improvement process begins with collecting data regarding the current condition of the business model, including customer profiles obtained through questionnaires and analysis of the business environment through literature studies. Next, a SWOT analysis is carried out to understand the strengths, weaknesses, opportunities and threats from internal and external aspects, as well as identifying the value proposition canvas to formulate the right strategy. Several proposals were put forward to solve problems such as in the Value Proposition block, proposals included increasing product variations, offering variations in glass sizes and toppings, as well as providing bundling packages. In the Customer Segments block, the focus is on increasing the number of Lembang customers. For Channels, proposals include increasing the use of online food delivery applications such as GoFood, increasing promotions via social media such as Instagram, adding the ShopeeFood and TikTok platforms, as well as displaying menu lists and linktr.ee on Instagram profiles. In the Customer Relationship block, proposals include offering discounts and promos, providing special promotions for local residents, as well as providing WiFi connections. In the Key Activities block, increasing sales and marketing activities, adding training and HR development programs, as well as improving indoor and outdoor facilities are priorities. In the Key Partners block, namely increasing cooperation with raw material suppliers. Meanwhile, in the Cost Structure block, the proposal includes additional costs for improving indoor and outdoor facilities, training and human resource development costs, as well as costs for WiFi connections. Lastly, in the Revenue Streams block, the focus is on increasing product sales offline and online.